Why we buy: the science of shopping - Underhill, Paco (New York: Simon y Schute, 1999)
Contents: 1. Instead of samoa, stores: the science of shopping, 2. walk like an aguption: the mechanics of shopping, 3. men are from sears hardware, women are from bloomingdale's: the demographics of shopping, se me, feel me, touch me, by me: the dynamics of shopping.
Keywords: Marketing - Shopping